2018
DOI: 10.1016/j.devcel.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

GRASP55 Senses Glucose Deprivation through O-GlcNAcylation to Promote Autophagosome-Lysosome Fusion

Abstract: The Golgi apparatus is the central hub for protein trafficking and glycosylation in the secretory pathway. However, how the Golgi responds to glucose deprivation is so far unknown. Here, we report that GRASP55, the Golgi stacking protein located in medial- and trans-Golgi cisternae, is O-GlcNAcylated by the O-GlcNAc transferase OGT under growth conditions. Glucose deprivation reduces GRASP55 O-GlcNAcylation. De-O-GlcNAcylated GRASP55 forms puncta outside of the Golgi area, which co-localize with autophagosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(151 citation statements)
references
References 59 publications
4
146
1
Order By: Relevance
“…Evidence for broad control of coat protein assembly and thus membrane traffic has been uncovered for coatomer protein complex (COP) II (COPII) and COPI‐mediated traffic between the ER and Golgi . Similarly, complex formation by proteins involved in tethering or fusion/fission of membranes such as SNAP‐29 and GRASP55 can be regulated by OGT, which can result in control of autophagosome interaction with endosome/lysosomes. Several proteins that are critical for clathrin‐mediated endocytosis and other mechanisms may be subject to O‐GlcNAc modification such as neuron‐enriched AP180 and its ubiquitously expressed homolog CALM and the endosomal clathrin adaptor AP3 is modified with O‐GlcNAc .…”
Section: Direct Control Of Endocytic Membrane Traffic By Metabolitesmentioning
confidence: 99%
“…Evidence for broad control of coat protein assembly and thus membrane traffic has been uncovered for coatomer protein complex (COP) II (COPII) and COPI‐mediated traffic between the ER and Golgi . Similarly, complex formation by proteins involved in tethering or fusion/fission of membranes such as SNAP‐29 and GRASP55 can be regulated by OGT, which can result in control of autophagosome interaction with endosome/lysosomes. Several proteins that are critical for clathrin‐mediated endocytosis and other mechanisms may be subject to O‐GlcNAc modification such as neuron‐enriched AP180 and its ubiquitously expressed homolog CALM and the endosomal clathrin adaptor AP3 is modified with O‐GlcNAc .…”
Section: Direct Control Of Endocytic Membrane Traffic By Metabolitesmentioning
confidence: 99%
“…GRASPs have a fundamental involvement in the stress‐induced UPS (more specifically, UPS types 3 and 4 ) but their exact role is still a matter of debate . A recent paper has suggested that GRASPs act as a tethering factor of autophagosome accessory proteins needed for the autophagosome–lysosome fusion and also on autophagosome maturation under glucose deprivation . Since nutrient starvation is one of the main activators of type 3 UPS, it has been suggested that GRASP might be recruited by the autophagosome and by the plasma membrane to enable the release of the UPS cargo, but this hypothesis is still to be proven.…”
Section: Introductionmentioning
confidence: 99%
“…Among all Golgi matrix proteins, the Golgi ReAssembly Stacking Proteins GRASP65 and GRASP55 (GRASPs, also called GORASP1 and GORASP2, respectively) are best characterized for their roles in Golgi structure formation, including stacking , Bekier et al 2017, Shin et al 2018, Barr et al 1997, ribbon-linking (Puthenveedu et al 2006;Tang et al 2016;Feinstein and Linstedt 2008), cargo transportation (Kuo et al 2000; Xiang and Wang 2010;Bekier et al 2017) • Golgi ribbon formation (Feinstein and Linstedt 2008) • Cell cycle control (Duran et al 2008) • Transport of specific cargo (Kuo et al 2000;D'Angelo et al 2009) • p24 cargo receptor retention • Autophagy (Zhang et al 2018;Zhang and Wang 2018a, b) • Unconventional secretion (Dupont et al 2011;Rabouille and Linstedt 2016;Vinke et al 2011;Gee et al 2011;Piao et al 2017)(Barr et al 1997;Xiang and Wang 2010;Bekier et al 2017;Shin et al 2018) • Golgi ribbon formation…”
Section: Golgi Reassembly Stacking Proteins (Grasps)mentioning
confidence: 99%
“…19.1). In addition, GRASP55 was reported to be involved in glucose starvation-induced autophagy (Zhang et al 2018 Fig. 19.1 Structure, modification, and binding sites on GRASP65 (a) and GRASP55 (b).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation